Tourism management dynamics : trends, management and tools - Costa, Carlos (Amsterdam ; London : Elsevier Butterworth-Heinemann, 2006)
Written by a team of globally renowned thinkers and researchers, this title provides the readers with an insight of the changes in the external business environment of tourism. It identifies key trends in the tourism industry. It also demonstrates how to apply trends, challenges and managerial techniques into the core of the tourism business.
Includes index.
Keywords: Tourism -- Management; Tourism -- Forecasting